Multi-objective system optimization method and experimental validation of a centralized squeeze film damper using a cell mapping method considering dynamic constraints. Issue 6 (3rd June 2021) - Zhang, Wei; Han, Bingbing; Li, Xiang; Sun, Jianqiao; Ding, Qian
Abstract : This article presents a multi-objective optimal design method for a squeeze film damper (SFD) with centring spring. The proposed method is able to obtain the optimal design parameters for a flexible rotor system. The objectives are minimizing the amplitude of the disk and transmitted force, and maximizing the SFD effectiveness simultaneously. These objectives generally conflict with each other, and the optimal values of the design parameters, or Pareto set, are obtained using the cell mapping method for different rotor imbalances with dynamic constraints. Three SFDs are designed and manufactured based on the obtained Pareto set, and experiments are conducted. The experimental results correspond with numerical simulation results, and the conflicting nature between objectives is validated in the case study. The proposed multi-objective optimization algorithm offers a novel and effective tool for designing SFDs. Engineers can refer to an optimal solution set with strong robustness against different demands, rather than a single design.